2021
DOI: 10.1002/ijgo.13990
|View full text |Cite
|
Sign up to set email alerts
|

Indirect impact of SARS‐CoV‐2 pandemic on pregnancy and childbirth outcomes: A nine‐month long experience from a university center in Lombardy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 79 publications
(240 reference statements)
0
4
0
Order By: Relevance
“…To date, very little evidence has been published regarding the impact of COVID-19 on the incidence of GDM stratified by gestational age of infection. In a retrospective analysis of prospectively collected data on uninfected and asymptomatic women, the authors concluded that pandemic-related control measures may have affected exercise levels in pregnant women, especially in those in their first and early second trimesters, thus ultimately favoring GDM [ 42 ]. This finding was further supported by a retrospective cross-sectional study, indicating that SARS-CoV-2 infection at the time of hospitalization for delivery did not significantly impact GDM because the parameter is a function of gestational age and changes over a longer period [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, very little evidence has been published regarding the impact of COVID-19 on the incidence of GDM stratified by gestational age of infection. In a retrospective analysis of prospectively collected data on uninfected and asymptomatic women, the authors concluded that pandemic-related control measures may have affected exercise levels in pregnant women, especially in those in their first and early second trimesters, thus ultimately favoring GDM [ 42 ]. This finding was further supported by a retrospective cross-sectional study, indicating that SARS-CoV-2 infection at the time of hospitalization for delivery did not significantly impact GDM because the parameter is a function of gestational age and changes over a longer period [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study showed that pregnant women who experienced lockdown had an increase in HbA1C in those with gestational diabetes and an increase in pregnancy-induced hypertension in normoglycemic women (17). Italian studies also have shown an increase in gestational diabetes during the pandemic (18,19). An Israeli study showed an increase in both hypertension and gestational diabetes during the pandemic (20).…”
Section: Maternal Morbiditiesmentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, the prevalence of GDM has increased compared to previous years [43][44][45]. Different theories regarding the pathophysiology of SARS-CoV-2 infection in relation to the occurrence of GDM have been proposed, including an increase in cases of newly diagnosed GDM or failure to comply with the first-line treatment for GDM due to worsening hyperglycemia (see next section).…”
Section: Current Evidence On the Association Between Covid-19 And Dia...mentioning
confidence: 99%